Granulocyte Colony-Stimulating Factor Alleviates Bacterial-Induced Neuronal Apoptotic Damage in the Neonatal Rat Brain through Epigenetic Histone Modification. (1st February 2018) - Yang, Yung-Ning; Su, Yu-Tsun; Wu, Pei-Ling; Yang, Chun-Hwa; Yang, Yu-Chen S. H.; Suen, Jau-Ling; Yang, San-Nan
Abstract : Bacterial meningitis during the perinatal period may cause long-term neurological deficits. The study investigated whether bacterial lipopolysaccharide (LPS) derived from E. coli. led to neuronal apoptosis with an impaired performance of long-term cognitive function involving the activation of histone modification in the TNF- α gene promoter. Further, we looked into the therapeutic efficacy of granulocyte colony-stimulating factor (G-CSF) in a neonatal brain suffering from perinatal bacterial meningitis. We applied the following research techniques: neurobehavioral tasks, confocal laser microscopy, chromatin immunoprecipitation, and Western blotting. At postnatal day 10, the animals were subjected to LPS and/or G-CSF. The target brain tissues were then collected at P17. Some animals (P45) were studied using neurobehavioral tasks. The LPS-injected group revealed significantly increased expression of NF- κ B phosphorylation and trimethylated H3K4 in the TNFA gene promoter locus. Furthermore, the caspase-3, neuronal apoptosis expression, and an impaired performance in cognitive functions were also found in our study. Such deleterious outcomes described above were markedly alleviated by G-CSF therapy. This study suggests that selective therapeutic action sites of G-CSF through epigenetic regulation in the TNFA gene promoter locus may exert a potentially beneficial role for the neonatal brain suffering from perinatal bacterial-induced meningitis.